ΔFosB is part of a homeostatic mechanism that protects the epileptic brain from further deterioration - Clasadonte, Jerome; Deprez, Tania; Stephens, Gabriel S.; Mairet-Coello, Georges; Cortin, Pierre-Yves; Boutier, Maxime; Frey, Aurore; Chin, Jeannie; Rajman, Marek (Frontiers in Molecular Neuroscience, 2024)
Activity induced transcription factor ΔFosB plays a key role in different CNS disorders including epilepsy, Alzheimer’s disease, and addiction. Recent findings suggest that ΔFosB drives cognitive deficits in epilepsy and together with the emergence of small molecule inhibitors of ΔFosB activity makes it an interesting therapeutic target. However, whether ΔFosB contributes to pathophysiology or provides protection in drug-resistant epilepsy is still unclear. In this study, ΔFosB was specifically downregulated by delivering AAV-shRNA into the hippocampus of chronically epileptic mice using the drug-resistant pilocarpine model of mesial temporal epilepsy (mTLE). Immunohistochemistry analyses showed that prolonged downregulation of ΔFosB led to exacerbation of neuroinflammatory markers of astrogliosis and microgliosis, loss of mossy fibers, and hippocampal granule cell dispersion. Furthermore, prolonged inhibition of ΔFosB using a ΔJunD construct to block ΔFosB signaling in a mouse model of Alzheimer’s disease, that exhibits spontaneous recurrent seizures, led to similar findings, with increased neuroinflammation and decreased NPY expression in mossy fibers. Together, these data suggest that seizure-induced ΔFosB, regardless of seizure-etiology, is part of a homeostatic mechanism that protects the epileptic brain from further deterioration.